THE INFLUENCE OF INTERGOVERNMENTAL REVENUE BUDGETS AND CLARITY OF BUDGET TARGETS ON THE FINANCIAL PERFORMANCE OF REGIONAL GOVERNMENTS: THE CASE OF THE REGIONAL APPARATUS ORGANIZATION OF THE CITY OF TIDORE ISLANDS - Madjodjo, Farid; Saleh, Charis Muhammad; Dahlan, Fadli (ACCOUNTABILITY, 2020)
This study aims to test the relationship of intergovernmental revenue and clarity of budget targets on the regional government financial performance. This study uses quantitative approach with primary data obtained from the results of distributing questionnaires and then measured by using a five-point Likert scale. The population of this study is the Regional Apparatus Organization which is official in the city of Tidore Islands, with the number of samples that have been determined as many as 45 samples. The sampling technique of this study is purposive sampling and conducts the multiple linear regression analysis as hypothesis testing. This study finds that the intergovernmental revenue and clarity of budget targets in partial have positive and significant effect on the regional government financial performance. The findings of this study imply that agency theory can explain the performance of local government of the City of Tidore Islands.